2021
DOI: 10.5209/rced.70917
|View full text |Cite
|
Sign up to set email alerts
|

Impact of absenteeism on academic performance under compulsory attendance policies in first to fifth year university students

Abstract: Since the implementation of the European Higher Education Area, universities have been obliged to implement continuous assessment systems that require a high degree of attendance by students. Using recorded data, from year 1 to year 5, of 694 students of a European university, where attendance is mandatory, the main objective of this research is to analyse to what extent absenteeism affects performance across the years of degree study. The investigation found a decreasing effect.  In addition, a cluster analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…This result was replicated in subsequent decades through various research studies conducted in different countries and universities (Credé et al, 2010). Most of the research in the social sciences has focused on students enrolled in economics and business administration courses (Chan et al, 1997;Maloney & Lally, 1998;Marburguer, 2001;Sauers et al, 2005;Méndez & Crespo, 2021). However, literature specifically addressing this phenomenon in the field of tourism appears to be absent.…”
Section: Literature Reviewmentioning
confidence: 93%
See 3 more Smart Citations
“…This result was replicated in subsequent decades through various research studies conducted in different countries and universities (Credé et al, 2010). Most of the research in the social sciences has focused on students enrolled in economics and business administration courses (Chan et al, 1997;Maloney & Lally, 1998;Marburguer, 2001;Sauers et al, 2005;Méndez & Crespo, 2021). However, literature specifically addressing this phenomenon in the field of tourism appears to be absent.…”
Section: Literature Reviewmentioning
confidence: 93%
“…The second group consists of research based on panel data (Rodgers, 2001;Latif & Miles, 2013). Lastly, the third group comprises studies that test this relationship through regression models (Romer, 1993;Maloney & Lally, 1998;Méndez & Crespo, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In his study, ref. [28] examined the relationship between absenteeism and academic performance across five years of a degree at a European university, where attending classes is mandatory. In analyzing data from 694 students over an academic year, the study revealed that absenteeism's negative impact on grades diminishes over the years, most notably affecting first-year students.…”
Section: Related Workmentioning
confidence: 99%